Bonds and Borders : Identity, Imagination and Transformation in Literature. - DeWald, Rebecca (Cambridge Scholars Publishing, 2011)
The essays in this collection exemplify the relevance of bonds and borders in literature and contribute each in their own individual ways to the discourse between literary studies and Border studies. The scope of contributions ranges from revisiting older works from colonial times to discovering current narratives in post-9/11 literature; from the search for a national identity in Welsh poetry to self-transformation and the trans-cultural journeys of individuals in the literature of migration ...